MONETARY POLICY CHALLENGES IN THE NEW NORMAL ERA: A SYSTEMATIC LITERATURE REVIEW - Arifin, Samsul; Sayifullah, Sayifullah (Jurnal Ilmu Ekonomi dan Pembangunan, 2022)
This paper aims to provide a systematic literature review (SLR) of studies conducted on the economic impact of the epidemic using the DSGE model. This research is guided by the PRISMA Preferred Reporting Items for Systematic Review and Meta-Analyses) statement, utilizing a systematic literature review (SLR) with Harzing's Publish or Perish software and Google Scholar as the primary sources, specifically focusing on the DSGE model's application. Under PRISMA, research is researched through three processes: 1) Defining clear research questions that allow systematic research, 2) Identifying inclusion and exclusion criteria, and 3) Examining a large database of scientific literature within a set time. A total of 11 out of 38 papers were identified and analyzed to provide a better understanding of the epidemiological model, the tradeoff of the lockdown policy between health and economy and the methodology adopted in the previous studies while the rest of the most recent studies appear to be related to the DSGE model with the adaptation of the epidemiological model during the Covid-19 pandemic. A total of four studies agree that many countries are imposing “lockdowns,” if not generally implementing “social distancing” to contain and potentially eliminate the virus.